Depression following fracture in women: a study of age-matched cohorts. Issue 2 (21st February 2014) - Williams, Lana J; Berk, Michael; Henry, Margaret J; Stuart, Amanda L; Brennan, Sharon L; Jacka, Felice N; Pasco, Julie A
Abstract : Objectives: High levels of disability, functional impairment and mortality are independently associated with fracture and depression, however the relationship between fracture and depression is uncertain. The aim of this study was to investigate whether fracture is associated with subsequent depressive symptoms in a population-based sample of women. Design: A study of age-matched fracture versus non-fracture cohorts of women. Setting: Barwon Statistical Division, southeastern Australia. Participants: Two samples of women aged ≥35 years were drawn from the Geelong Osteoporosis Study (GOS). The fracture cohort included women with incident fracture identified from radiology reports and the non-fracture cohort were randomly selected from the electoral roll during 1994–1996. Outcome measure: Symptoms of depression for women with and without fracture during the 12-month period 2000–2001 were identified by self-report questionnaire based on the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) criteria. Results: A total of 296 women with fracture (12 hip, 48 vertebral, 91 wrist/forearm, 17 upper arm, 7 pelvis, 11 rib, 62 lower leg and 48 other fractures) and 590 women without fracture were included. Associations between fracture and depression differed between younger (≤65 years) and older (>65 years) women. Age and weight-adjusted odds ratio for depression following fracture among younger women was 0.62 (0.35 to 1.11, p=0.12) and 3.33 (1.24 to 8.98, p=0.02) for older women. Further adjustment for lifestyle factors did not affect the results. Conclusions: This study demonstrated that differences in mood status exist between older and younger women following fracture and that fracture is associated with increased depression in older women. Assessment of mood status in both the short and long term following fracture in the elderly seems justified, with early detection and treatment likely to result in improved outcomes.